THE INFLUENCE OF LIFESTYLE, PRODUCT PRICES, QUALITY AND BRAND ON INTEREST TO BUY SECOND BRANDED CLOTHING: Case Study on Semester VII STIE Bina Karya Tebing Tinggi Students - Etri Jayanti, Suci; Margareth, Yomeini; Siahan, Rumiris (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study aims to determine the effect of lifestyle, product prices, quality and brand on the interest in buying second branded clothes (a case study on STIE Bina Karya Tebing Tinggi students). this type of research is an associative quantitative research type and distributes questionnaires through a google form platform to respondents who are sampled for this research and then the data is processed using SPSS (Statistical Product and Service Solution) version 25.00. This study used a sample of 34 respondents. Sampling using purposive sampling technique. The test tools used are instrument test, classical assumption test and hypothesis test. From the results of this test, it can be concluded that based on the results of the analysis of the first hypothesis, it can be seen that tcount (0.960) < ttable (2.042), Likewise, with a significance value of 0.345 <0.05, it can be concluded that the first hypothesis is rejected, meaning that the Lifestyle Variable (X1) has no significant effect on Purchase Interest (Y). The second hypothesis can be seen that tcount (2.064) > ttable (2.042), and the significance value is 0.048 <0.05, it can be concluded that the second hypothesis is accepted, meaning that Product Price (X2) has an effect on Purchase Interest (Y). The third hypothesis can be seen that tcount (2.538) > ttable (2.042), and the significance value is 0.017 <0.05, it can be concluded that the third hypothesis is accepted, meaning that Quality (X3) has an effect on Purchase Interest (Y). The fourth hypothesis can be seen that tcount (-0.094) > ttable (2.042), and the significance value is 0.926 <0.05, it can be concluded that the fourth hypothesis is rejected,